The role of land office and forestry department to prevent forest offences in Negeri Sembilan - Tham, Sikh Bing, 1987-, author; Mohammad Tahir Sabit; Fakulti Geoinformasi dan Harta Tanah (2011)
Project Paper (Sarjana Muda Sains (Pentadbiran dan Pembangunan Tanah)) - Universiti Teknologi Malaysia, 2011